Potrzeba reedukacji chodu po udarze niedokrwiennym mózgu = Need re-educating gait after ischemic brain - Strojek, Katarzyna; Janczak, Łukasz; Radzimińska, Agnieszka; Kaźmierczak, Urszula; Piekorz, Zuzanna; Strączyńska, Agnieszka; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Strojek Katarzyna, Janczak Łukasz, Radzimińska Agnieszka, Kaźmierczak Urszula, Piekorz Zuzanna, Strączyńska Agnieszka, Zukow Walery. Potrzeba reedukacji chodu po udarze niedokrwiennym mózgu = Need re-educating gait after ischemic brain. Journal of Education, Health and Sport. 2016;6(10):79-89. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.160238 http://ojs.ukw.edu.pl/index.php/johs/article/view/3929 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 12.10.2016. Potrzeba reedukacji chodu po udarze niedokrwiennym mózgu Need re-educating gait after ischemic brain Katarzyna Strojek¹, Łukasz Janczak¹, Agnieszka Radzimińska¹, Urszula Kaźmierczak¹, Zuzanna Piekorz¹, Agnieszka Strączyńska¹, Walery Zukow2 1. Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Bydgoszcz, Polska 2. Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz, Polska Słowa kluczowe: reedukacja chodu, udar niedokrwienny mózgu Keywords: gait re-education, ischemic stroke Streszczenie Celem pracy jest zwrócenie uwagi na celowość reedukacji chodu u pacjentów po przebytym udarze mózgu. W pracy zostały przedstawione odchylenia od normy w poszczególnych pod fazach cyklu chodu oraz zaprezentowane najważniejsze metody reedukacji chodu. Udar mózgu stanowi jedną z najczęstszych chorób neurologicznych i powoduje wiele zaburzeń związanych z fizjologicznym chodem. Chód pacjentów po przebytym udarze mózgu objawia się brakiem symetrii podczas poszczególnych faz cyklu chodu, nierównym obciążeniem kończyn oraz zaburzoną długością kroku. Reedukacji chodu ma na celu przywrócenie fizjologicznych wzorców chodu, zbudowanie prawidłowego napięcia mięśniowego w kończynie niedowładnej, poprawę równowagi oraz przywrócenie funkcji samodzielnego i bezpiecznego poruszania się. Abstract The aim of the work is to draw attention to the desirability of re-educating gait in patients after stroke of the brain. At work were presented to the deviation in each subphases power cycle and presented the most important method of re-educating gait. Stroke is one of the most common neurological diseases and causes many physiological disorders related to your vehicle. Gait of patients after stroke of the brain revealed by the lack of symmetry while the individual phases of the gait cycle, the uneven load of limbs and impaired the length of the step. Gait re-education is designed to restore the physiological gait patterns, to build proper muscle tone in the affected paretic limb, improving balance and restore the functions of independent and safe move.